Changes in sprint-related outcomes during a period of systematic training in a girls' soccer academy - Wright, M. D.; Atkinson, G. (The Journal of Strength and Conditioning Research, 2019)
The longitudinal tracking of performance indicators is lacking during the training of young female soccer players. Therefore, changes in 5-m acceleration, 20-m speed, change-of-direction (COD) speed, and repeated-sprint ability (RSA) were quantified during a 3-year period in an English Football Association Center of Excellence. Fourteen players (mean age = 12.1 years, SD = ±0.9) were recruited, and their best performance scores from preseason and in-season testing were averaged. Players were typically exposed to soccer (2 × 90 minutes per week) and strength and conditioning training (1 × 70 minutes per week) and played 20 soccer matches (50-80 minutes) during 35-week seasons. Mean (±90% confidence limits (CL)) overall improvements over the 3 years were 5.9% (1.3) (most likely large) for speed, 4.0% (1.0) (most likely large) for RSA, 8.8% (1.1) for acceleration, and 8.3% (1.4) for COD speed (both most likely very large). Improvements between years one and 2 ranged from most likely moderate to very large. Further small improvements in COD speed and 20-m speed (both likely) were observed between years 2 and 3. Individual differences in response were apparent only for COD speed, which were moderate and small between years 2 and 3. Most likely very large to near-perfect within-player correlations were observed between maturation and sprint measures. These data from a single-arm longitudinal study indicate that systematic exposure to training, which includes one dedicated strength and conditioning session each week, is associated with improvements in sprint-related physical qualities in girls.